REHABILITACJAAssessment of the effects of preparatory in-home, and hospital physiotherapy, on patients before surgery of lung parenchyma - Bal-Bocheńska, Monika; Kądziołka, Wojciech; Kądziołka, Joanna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Aim: Assessment of respiratory function improvement with spirometric limit values in patients who were being prepared for the resection of lung, and who were involved in an identical physiotherapy programme, at home and in a rehabilitation department. Material and Methods: 10-day pre-surgery physiotherapy programme for 50 patients chosen at random. In the first examination which qualified for the surgery, the patients had limited spirometric values. They were randomly divided into two equal groups A and B, each of the groups including 25 patients. Group A included those patients who were being prepared by the therapist in the physiotherapy department, during their stay in the hospital. Group B consisted of the patients who were performing the exercise programme on their own, at home. The procedure designed in the way mentioned above was performed for a period of 10 days, 3 times a day, in both groups of patients. Results: The employment of the 10-day pre-surgery physiotherapy programme in group A resulted in an improvement of spirometric values. Increase of VC% amounted to 25.6%, and FEV1 increased by 23.9%, which enabled another analysis of respiratory function to be performed, and as a result allowed 25 patients from this group to be qualified for the surgery. However, in group B the same improvement did not occur. VC% increased by 7.8%, and FEV1 by 10.9%. Only 11 patients from this group qualified for the surgery, whereas the others underwent the exercise programme in the physiotherapy office of the hospital again. Conclusions: 1. The conducted research has proved the pre-surgery physiotherapy performed in hospital to be fully justified. 2. The intended improvement of spirometric values was not obtained in group B, consisting of patients who had been prepared for surgery at home. This was due to the lack of regularity or patients giving up exercising when not supervised. 3. In group A, consisting of patients prepared at hospital, significant improvement of respiratory values was noted. That fact qualified the patients for surgical treatment and constituted the evidence that the presented programme was highly valuable.